Pajak Rokok Dalam Kebijakan Anggaran Kesehatan Di Provinsi Jawa Barat - Rizki Rusmana Putra (Department of Public Administration, 2021)
Taxes are the country's largest source of income. Cigarettes are one of the goods that are subject to excise, and the results of cigarette excise are included in taxes for the region. The regulation on cigarettes has two opposite sides and traps in quite a dilemma. On the one hand, the cigarette tax provides a significant income for a region. Still, on the other hand, the government must also be responsible for the negative impact of cigarettes on the health of its consumers, which increases the budget for health facilities. In regulation, cigarette taxes that enter local government revenues apply a minimum of 50% to enter health service funding. This research was conducted at the Regional Revenue Agency (BAPENDA) of West Java Province and the West Java Provincial Health Office. This research uses descriptive research methods and a qualitative approach. The use of cigarette taxes in West Java has been appropriate for the inclusion of cigarette tax results in the health budget, but the disbursements are still not optimal. The West Java Health Office focuses on the fulfillment of medical devices to deal with the harmful effects of smoking on society. Meanwhile, local governments should be better at absorbing the budget from cigarette taxes to be effective and efficient in their use. Then there needs to be socialization to the public regarding the special cigarette tax allocation for the health budget.